From personal to global: Understandings of social accountability from stakeholders at four medical schools. (2nd October 2016) - Preston, Robyn; Larkins, Sarah; Taylor, Judy; Judd, Jenni
Abstract: Aim : This paper addresses the question of how social accountability is conceptualised by staff, students and community members associated with four medical schools aspiring to be socially accountable in two countries. Methods : Using a multiple case study approach this research explored how contextual issues have influenced social accountability at four medical schools: two in Australia and two in the Philippines. This paper reports on how research participants understood social accountability. Seventy-five participants were interviewed including staff, students, health sector representatives and community members. Field notes were taken and a documentary analysis was completed. Results : Overall there were three common understandings. Socially accountable medical education was about meeting workforce, community and health needs. Social accountability was also determined by the nature and content of programs the school implemented or how it operated. Finally, social accountability was deemed a personal responsibility. The broad consensus masked the divergent perspectives people held within each school. Conclusion : The assumption that social accountability is universally understood could not be confirmed from these data. To strengthen social accountability it is useful to learn from these institutions' experiences to contribute to the development of the theory and practice of activities within socially accountable medical schools.